Functional Verification Coverage Measurement and Analysis - Piziali, Andrew. (Springer US, 2008)
Functional Verification Coverage Measurement and Analysis addresses a means of quantitatively assessing functional verification progress. Without this process, design and verification engineers, and their management, are left guessing whether or not they have completed verifying the device they are designing. Using the techniques described in this book, they will learn how to build a toolset which allows them to know how close they are to functional closure. Functional Verification Coverage Measurement and Analysis is the first book to introduce a useful taxonomy for coverage metric classification. Using this taxonomy, the reader clearly understands the process of creating an effective coverage model. A must read! - Harry Foster, Jasper Design Automation, Co-Author of Assertion-Based Design Andrew's book is the most thoughtful and comprehensive treatment of coverage I have seen. I recommend reading (and re-reading) this book to anybody who is really serious about functional verification. - Yoav Hollander, CTO, Verisity Design In the last few years, coverage has become a must in hardware verification and in software testing. From having to push people to use coverage, the situation changed to great interest... Andrew's excellent and comprehensive book on coverage, the first of its kind, could not have come at a better time. -Shmuel Ur, Research Scientist, IBM.